Multiple evolutionary origins of high mountain bellflowers with solitary flowers and calyx scales render a core Caucasian clade of the Scapiflorae group (Campanulaceae). Issue 7 (3rd October 2019) - Silakadze, Nana; Kilian, Norbert; Korotkova, Nadja; Mosulishvili, Marine; Borsch, Thomas
Abstract : Campanula is one of the species-rich genera of the bellflower family (Campanulaceae), in a wider sense with ∼600 species, growing in a wide range of habitats in the northern hemisphere. The Caucasus is one of the areas with especially many endemic Campanula species. The Scapiflorae group comprises alpine and subalpine perennial rocky plants, which develop numerous short single-flowered stems from a basal leaf rosette. In its current circumscription based on the comparative analysis of selected morphological characters, it consists mostly of species endemic to the Caucasus, and some in the Alps and North-East Asia, and it is classified as C. subg. Scapiflorae . We performed a molecular phylogenetic analysis including a dense sampling of C. subg. Scapiflorae and other Caucasian Campanula species and representatives of the large Eurasian Campanula CAM17 clade. Campanula subg. Scapiflorae is non-monophyletic in its current circumscription, but the Caucasian species of this group form a well-supported clade. Ancestral character state reconstruction across the Eurasian CAM17 clade shows that unbranched inflorescences, a basal leaf rosette, calyx appendages and a perennial life form with numerous low stems, which is characteristic for the Scapiflorae group, evolved convergently at least five times in unrelated high mountain species such as C. alpina or C. petrophila . The Caucasian clade comprises four major sublineages in our analyses, suggesting complex biogeographic patterns among the Greater and Lesser Caucasus mountain ranges.